2021
DOI: 10.48550/arxiv.2105.08090
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparing different closure relations for cosmic ray hydrodynamics

Timon Thomas,
Christoph Pfrommer

Abstract: Cosmic ray (CR) hydrodynamics is a (re-)emerging field of high interest due to the importance of CRs for the dynamical evolution of the interstellar, the circumgalactic, and the intracluster medium. In these environments, CRs with GeV energies can influence large-scale dynamics by regulating star formation, driving galactic winds or by altering the pressure balance of galactic halos. Recent efforts have moved the focus of the community from a one-moment description of CR transport towards a two-moment model as… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Jiang & Oh (2018) resolve this issue by solving two-moment formulation of the CR equations, facilitating the integration of CR transport in both streaming and diffusion limits. Thomas & Pfrommer (2019) and Chan et al (2019) also explore CR two-moment implementations with slightly different approaches. Thomas & Pfrommer (2021) compares closure relations for CR two-moment equations and found that the impact is small in the streaming limit, where scattering is neglected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jiang & Oh (2018) resolve this issue by solving two-moment formulation of the CR equations, facilitating the integration of CR transport in both streaming and diffusion limits. Thomas & Pfrommer (2019) and Chan et al (2019) also explore CR two-moment implementations with slightly different approaches. Thomas & Pfrommer (2021) compares closure relations for CR two-moment equations and found that the impact is small in the streaming limit, where scattering is neglected.…”
Section: Introductionmentioning
confidence: 99%
“…Thomas & Pfrommer (2019) and Chan et al (2019) also explore CR two-moment implementations with slightly different approaches. Thomas & Pfrommer (2021) compares closure relations for CR two-moment equations and found that the impact is small in the streaming limit, where scattering is neglected. Hopkins et al (2021a) derive and implement moment-equations that can also handle CRs in the strong scattering limit with generalized source terms.…”
Section: Introductionmentioning
confidence: 99%